Mitochondrial DNA control region diversity in a population from Espirito Santo state, Brazil - Sanches, Naiara M. [UNESP]; Paneto, Greiciane G.; Figueiredo, Raquel F. [UNESP]; Mello, Aline O. de [UNESP]; Cicarelli, Regina M. B. [UNESP] (Springer, 2014)
Mitochondrial DNA (mtDNA) analysis has proved to be useful for forensic identification, especially in cases which nuclear DNA markers fail, as in degraded samples or in cases where the biological material has few traces or no nuclear DNA. Moreover, it can be applied in population genetics, inferring the origin of a population. In this work, the entire mtDNA control region of 97 individuals from the state of Espirito Santo, Brazil, was analyzed. We have found 94 different haplotypes yielding a high haplotype diversity of 0.9994 +/- A 0.0016. The probability of a random match calculated was 1.09. Haplogroup distribution analysis confirmed a highly admixed Latin American population: African lineages (43.3 %), European lineages (32.0 %), Native American lineages (23.7 %) and Asian lineages (1.0 %). We have concluded that this type of tool can be used both in forensic genetics to the study of different human populations, such as highly admixed populations, and in the study of migration's history and colonization of different states and countries of the world.
Keywords: Mitochondrial DNA; Control region; Haplogroup; Espirito Santo; Brazil